Prakiraan Daerah Penangkapan Ikan Di Selat Bali Berdasarkan Data Citra Satelit - Iqbal Ghazali; Abdul Manan (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2011)
Indonesia has a lot of potential marine ecosystem and fisheries, this condition make some many Indonesian get a occupation to be fisherman. However, that is make a problem during his fishing activity, so we have to make some sophisticated technology to support that is activity. At the time, remote sensing technology is the answer for they problem, it is because of that is technology fisherman can be improvement they catcher with more efficient. Determination of fishly ground area by remote sensing technology has some stage before arranging layout Fishly Ground Area Estimation (FGAE) map. Procedure to arranging are respectively data searching, data processing, and data analysis, and the last stage is composing of layout of FGAE map.The main purpose of this study is to know about catching area at Bali straits based on image satellite with creating layout of FGAE map. This activity doing descriptive method and the value are based on observation, interview, active participation, and literature search data. At the PDPI making process, the chlorophyl-a data and sea surface temperature getting important parameter, which temperature is the main to parameter to understand of front area and upwelling which is have a lot of nutrient composition. In the other hand, chlorophyl-a is also parameter to know of prosperity area. The data of current, wind speed, wave, and sea surface level are important component as supporting data that will be help to fisherman on determination of fishing ground area at helping fisherman in catching activity. Keywords: Fishing ground, Remote sensing, Bali straits, Chlorophyl-a, Sea surface temperature